ANALISIS HASIL PENGUJIAN KAYU YANG DISERANG PENGGEREK KAYU DI LAUT DENGAN INTERPRETASI GAMBAR DIGITAL - Krisdianto; Listya Mustika Dewi; Mohammad Muslich (Jurnal Penelitian Hasil Hutan, 2015)
Natural durability is determined through the tests of wood against wood attacking organisms. Natural durability of wood against marine borer was tested by exposing wood into the open sea water for six months. Damage intensity can be measured on the basis of digital image using Image-J software. This paper studies natural durability of nine wood species from Sumatera, Java and Kalimantan against marine borer. Results show that sempur lilin (Dillenia obovata Hoogl.), bambang lanang (Michelia champaca L.var. pubinervia) and kayu babang (Azadirachta excelsa (Jack) Jacobs) were classified into class durability I (very resistant), while cangcaratan (Lithocarpus sundaicus (Blume) Rehd. and avengekalakai (Shorea pervustipulata ssp. albifolia) were classified into class durability II (resistant) against marine borer. Ki pasang (Prunus javanica Miq.) and segelam (Hopea rudiformis) were grouped into class durability III (moderately resistant), while ki biwang (Arthophylum diversifolium Blume) and ki langir (Otophora spectabilis Blume) fall into class durability V (perishable). Damage intensity could be measured accurately using Image-J software. However, this method obtained higher damage percentage since the ex-rope hole was included in the measurement. Accordingly, the image method should be modified by excluding the ex-rope image to achieve high accuracy measurement.